Poetic Structure as Cultural Renewal: A Structuralist Study of Adonis’s Bayt - Ekawati; Syafa Billa Annisa Fitri; Aditiya Royhan Pratama; Muhammad Hakim (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
This study examines Adonis’s poem Bayt through a structuralist approach to reveal how its textual construction represents the transition from tradition to modernity in modern Arabic literature. Adonis, as a pioneer of Arab modernism, reinterprets classical poetic forms by emphasizing symbolism, free expression, and philosophical reflection. The research aims to identify the external and internal structures of Bayt—covering diction, imagery, and metaphors—and to explain how these elements embody the aesthetics of modern Arabic poetry. Using a descriptive qualitative method, data were collected from Adonis’s poetry text and analyzed by applying structuralist theory to explore intrinsic relationships among form, meaning, and symbol, supported by a historical perspective. The findings show that Bayt abandons classical metre and rhyme in favor of free verse and internal rhythm, while its themes reflect identity, collective memory, and existential continuity. The study concludes that Bayt is not merely aesthetic but philosophical, offering social reflection and cultural renewal. Its novelty lies in linking structuralist textual analysis with modern Arabic literary transformation, suggesting further comparative research on Adonis’s poetic influence in Arab modernism.